RELIGIOUS PROPER NAMES IN THE HUTSUL DIALECTS (BASED ON THE MATERIAL OF THE WORK «HUTSUL WORLDS. LEXICON») - Tsyperdiuk, O. D. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
In the article the presentation of Christian religious proper names in the lexical structure of the Hutsul dialects is examined. The main groups of religious proper names are analyzed; their lexical and semantic features, structural peculiarities, word building connections and phraseological activity are observed.